2014
DOI: 10.1016/j.ophtha.2013.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Amblyopia in the Vision in Preschoolers Study

Abstract: Objective To evaluate risk factors for unilateral amblyopia and for bilateral amblyopia in the Vision In Preschoolers (VIP) Study. Design Multicenter, cross-sectional Study. Participants Three- to 5-year old Head Start preschoolers from 5 clinical centers, over-representing children with vision disorders. Methods All children underwent comprehensive eye exams including threshold visual acuity (VA), cover testing, and cycloplegic retinoscopy, performed by VIP-certified optometrists and ophthalmologists wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 21 publications
1
90
1
8
Order By: Relevance
“…36–38 One common thread throughout these studies is the dramatic increase in risk for bilateral amblyopia at a threshold of +4 to +5D of hyperopic refractive error. 3335 This same level of uncorrected hyperopia (+4D) has been shown to be associated with increased accommodative lags and more variable accommodative responses in infants and preschool children. 39, 40 Thirdly, a large-scale study of emmetropization in infants found that the probability of emmetropization drops to 50% with hyperopic refractive error of +5D at 3 months of age.…”
Section: Discussionmentioning
confidence: 97%
“…36–38 One common thread throughout these studies is the dramatic increase in risk for bilateral amblyopia at a threshold of +4 to +5D of hyperopic refractive error. 3335 This same level of uncorrected hyperopia (+4D) has been shown to be associated with increased accommodative lags and more variable accommodative responses in infants and preschool children. 39, 40 Thirdly, a large-scale study of emmetropization in infants found that the probability of emmetropization drops to 50% with hyperopic refractive error of +5D at 3 months of age.…”
Section: Discussionmentioning
confidence: 97%
“…In humans, amblyopia is comparatively rare in exotropia and the onset of ocular misalignment occurs at a later age than in esotropia (Chia et al 2007;Mohney 2007;Pascual et al 2014). Children usually enjoy normal visual function through infancy but then develop an intermittent exotropia that eventually decompensates into a constant exotropia in some individuals (Buck et al 2012;Choi and Kim 2013;Mohney and Huffaker 2003;Nusz et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…11 Pascual et al recently reported that bilateral hyperopia was associated with increased odds of bilateral amblyopia in preschool children enrolled in the VIP study (odds ratio of 9.4 for bilateral hyperopia ≥ +4 D, reference level 0.00 to < +1 D, p<0.0001). 12 A recent population based study showed an increased prevalence of strabismus and amblyopia in 6- and 12-year-old children with moderate hyperopia. 13 Longitudinal studies have also supported an association between hyperopia and strabismus and/or amblyopia.…”
mentioning
confidence: 98%